2018
DOI: 10.1136/bcr-2017-221995
|View full text |Cite
|
Sign up to set email alerts
|

Unusual congenital coronary artery anomaly in a young adult presenting as sudden cardiac arrest

Abstract: A previously asymptomatic young female with no previous medical or cardiac history collapsed during indoor exercise. A portable automatic external defibrillator showed a shockable rhythm. She received multiple electrical shocks with return to normal sinus rhythm without ischaemic ECG changes. Her troponin level was mildly elevated. A transthoracic echocardiogram revealed moderately reduced left ventricular ejection fraction with global hypokinesis. During emergent coronary angiography, the left main coronary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Young adults generally have more OHCA due to coronary artery disease (CAD) than younger groups, and more OHCA due to genetic factors than older groups. Young adults generally have more OHCA due to CAD than younger groups, and more OHCA due to genetic factors than older groups [ 37 , 38 , 39 ]. Therefore, the patterns of impact of the first responder, bystander CPR, and AED use are located between the younger and the older.…”
Section: Discussionmentioning
confidence: 99%
“…Young adults generally have more OHCA due to coronary artery disease (CAD) than younger groups, and more OHCA due to genetic factors than older groups. Young adults generally have more OHCA due to CAD than younger groups, and more OHCA due to genetic factors than older groups [ 37 , 38 , 39 ]. Therefore, the patterns of impact of the first responder, bystander CPR, and AED use are located between the younger and the older.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study from Thailand by Kultida et al (2018) [4] has reported the absence of the left main coronary artery and left circumflex artery in 0.4% cases. Cortes et al (2018) [5] have recently reported a case of congenital absence of left coronary artery, causing a sudden cardiac arrest during indoor exercise. A case of congenital absence of left circumflex artery with the presence of a super dominant right coronary artery has also been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical diagnosis of LMCAA might be neglected due to the wide range of nonspecific presenting symptoms including chest pain in a young patient, dyspnea, syncope or aborted sudden cardiac death 2, 5, 6, 7. Patients could remain asymptomatic for a long time due to a well development collateral system.…”
Section: Discussionmentioning
confidence: 99%